Analisis Pengaruh Mutu Pelayanan Program Kartu Indonesia Pintar Atau Kartu Indonesia Sehat Terhadap Kepuasan Masyarakat Di Kecamatan Manggala Makassar - Rusli, Muh. (Patria Artha Management Journal, 2020)
This study aims to determine the Analysis of Service Quality Influence on Satisfaction of Society in Makassar manggala district. The results from this research that the influence of physical evidence, reliability,, assurance and empathy have influence with the satisfaction of society. Suggestion to Mr. Manggala Makassar sub-district head should increase the effort to develop human resource skill both in quantity and quality.